Mutagenicity of Pueraria mirifica Airy Shaw & Suvatabandhu and antimutagenicity of Thunbergia laurifolia Linn. - Saenphet K. (2014)
Thunbergia laurifolia Linn has been reputed to have antitoxic effects for all toxic substances. In this present study, we evaluated its effect against the mutagenicity induced by aqueous extracts from Pueraria mirifica Airy Shaw & Suvatabundhu in male rats. The formation of micronuclei in polychromatic erythrocytes was induced by oral administration of an aqueous extract of P. mirifica at the doses of 400, 600, and 800 mg/kg to the rats for 30 days. The results were that the extracts of P. mirifica at doses of 600 and 800 mg/kg acted as a mutagenic agent by inducing higher frequencies of micronuclei as compared to the controls. For the antimutagenic test, P. mirifica extract at a dose of 600 mg/kg (minimal effective dose) was mixed with fresh and dried extracts of T. laurifolia in proportions of 7:3 and 1:1, respectively. The results of 4-week-treatment indicated that aqueous extracts of T. laurifolia, prepared by both fresh and dry methods, could significantly inhibit the induction of micronuclei as induced by P. mirifica. It could be concluded from the results that, under certain circumstances, T. laurifolia exhibits a significant antimutagenic activity. The use of P. mirifica and T. laurifolia as fusion herbal medicines is suggested.